A New Neotropical Species of Monohelea Kieffer from Uruguay (Diptera: Ceratopogonidae) - Maria Luiza Felippe-Bauer; Gustavo R Spinelli (Memorias do Instituto Oswaldo Cruz, 1998)
A new species of Monohelea Kieffer, M. uruguayensis, is described and illustrated from a male specimen from Uruguay